2009
DOI: 10.2500/ajra.2009.23.3253
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effect of Smoking and Nasal Septal Deviation on Mucociliary Clearance and Improvement after Septoplasty

Abstract: Nasal septal deviation and smoking deteriorates nasal MCC time and this result can be shown easily with the saccharine test. Properly performed septoplasty surgery decreases nasal MCC time during the late postoperative period but MCC times are still longer than normal. The saccharine test can be used for following up the effect of septoplasty upon nasal mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 35 publications
1
45
0
2
Order By: Relevance
“…They also found that there is no significant difference in mucociliary clearance time between obstructed nasal cavity and the non-obstructed side. In the study by Kamaran and Tek [6], the test side was selected randomly .Similarly in our study it was found that there was no significant difference in the mucociliary clearance between the obstructed and the non-obstructed sides.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…They also found that there is no significant difference in mucociliary clearance time between obstructed nasal cavity and the non-obstructed side. In the study by Kamaran and Tek [6], the test side was selected randomly .Similarly in our study it was found that there was no significant difference in the mucociliary clearance between the obstructed and the non-obstructed sides.…”
Section: Discussionsupporting
confidence: 61%
“…In our study, patients showed improvement in the symptoms at the end of 6 weeks after surgery. There was a statistically significant decrease at the postoperative mucociliary clearance time among the non-smoker patients who underwent surgery when compared with preoperative mucociliary clearance time [6]. Kamaran and Tek concluded that if the septoplasty procedure is properly performed, nasal mucociliary clearance significantly improves.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Active cigarette smoking is associated with a decrease in mucociliary clearance measured based on saccharine transit time 21 and has been shown to have a negative effect on mucosal recovery after endoscopic sinus surgery in adults and children. [22][23][24][25] In a study using the Third National Health and Nutrition Examination Survey (1988-1994) of 33,994 persons, Lieu and Feinstein 26 examined the relationship between chronic sinusitis, active cigarette smoking, and secondhand smoke (SHS) exposure.…”
Section: Active and Secondhand Cigarette Smokingmentioning
confidence: 99%
“…In the first group we have primary (genetic) and secondary (infection or inflammation) ciliary diskinesia while in the second group we found cystic fibrosis, COPD, or asthma patients. Many factors influence the MCC, among them are: temperature, humidity, trauma, smoking, viral infections, chronic sinusitis, allergic rhinitis, adenoid hypertrophy, deviated septum, sinus surgery, fibrosis cystic, chronic bronchitis and asthma [23]. At present, none of the methods studying MCC is the ideal, and there is a variety of investigational methods and techniques for its study.…”
Section: Mucociliary Clearance (Mcc)mentioning
confidence: 99%